2018
DOI: 10.1002/14651858.cd000996.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids for bronchiectasis

Abstract: Editorial group: Cochrane Airways Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 5, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 71 publications
0
35
1
1
Order By: Relevance
“…A recent Cochrane review included seven studies with 380 adults describing no significant differences from baseline in FEV 1 , average exacerbation frequency or QoL when used for 6 months or less. 64 A single study similarly showed no significant difference in FEV 1 or other clinical parameters after 12 months. One trial in 40 adults used high-dose inhaled budesonide for 3 months and then randomized to 3 months continued high-dose budesonide or medium-dose budesonide with a longacting beta-agonist.…”
Section: Who Should Receive Macrolides and Which One For How Long?mentioning
confidence: 92%
See 3 more Smart Citations
“…A recent Cochrane review included seven studies with 380 adults describing no significant differences from baseline in FEV 1 , average exacerbation frequency or QoL when used for 6 months or less. 64 A single study similarly showed no significant difference in FEV 1 or other clinical parameters after 12 months. One trial in 40 adults used high-dose inhaled budesonide for 3 months and then randomized to 3 months continued high-dose budesonide or medium-dose budesonide with a longacting beta-agonist.…”
Section: Who Should Receive Macrolides and Which One For How Long?mentioning
confidence: 92%
“…There is an overlap of patients with asthma, COPD and bronchiectasis but with airway inflammation present in all and many having asthma‐like symptoms, inhaled corticosteroids may be potentially useful in all. A recent Cochrane review included seven studies with 380 adults describing no significant differences from baseline in FEV 1 , average exacerbation frequency or QoL when used for 6 months or less . A single study similarly showed no significant difference in FEV 1 or other clinical parameters after 12 months.…”
Section: Long‐term Treatments Of Bronchiectasismentioning
confidence: 99%
See 2 more Smart Citations
“…376 Recently, the role of ICS alone for preventing exacerbations was reviewed using the same Cochrane methodology. 377 It concluded that there is insufficient evidence to support the routine use of ICS in adults with stable state bronchiectasis.…”
mentioning
confidence: 99%